Towards a hierarchy of consumption behaviour in the circular economy. Issue 3 (June 2019) - Maitre-Ekern, Eléonore; Dalhammar, Carl
In their roles as purchasers, users and dischargers of used products, consumers play an important role in the circular economy. In this article, we put forward a 'hierarchy of consumption behaviour' to support European Union policymaking. Among the priorities are avoiding the purchase of single-use and unnecessary products, prolonging the lifetime of products through maintenance and engaging in repair activities. Moreover, the hierarchy intends to privilege sharing and leasing to buying and second-hand products to new ones. Finally, consumption in the circular economy also requires allowing products to re-circulate. Changing consumption patterns is difficult insofar as they are largely determined by the paradigm upon which our economy is built and are enabled by the existing legal framework, most notably European Union consumer law. The article contains concrete recommendations to develop European Union law and promote the proposed hierarchy.